Teaching bahasa Indonesia to non-native speakers: Strategies, challenges, and innovations - Susanto, Budi; Adnyana, Ida Bagus Artha; Dizon Jr, Rodolfo P.; Ghafar, Zanyar Nathir; Idri, Nadia; Ajayi, Temitope Michael (Journal of Language, Literature, Social and Cultural Studies, 2025)
Teaching Bahasa Indonesia to non-native speakers has gained increasing significance in the context of global mobility, academic exchange, and cross-cultural communication. As Indonesia’s geopolitical and economic influence grows, so too does the demand for high-quality language instruction that not only develops linguistic competence but also fosters intercultural understanding. This article examines the strategies, challenges, and innovations involved in teaching Bahasa Indonesia as a foreign language, with an emphasis on pedagogical approaches that are adaptable to diverse learner profiles. Drawing on a review of current literature and practical case studies, the study identifies communicative, task-based, and culture-integrated methodologies as effective strategies to enhance learner engagement and retention. Key challenges include limited teaching resources tailored for non-native learners, variations in learners’ first-language backgrounds, and the need to balance linguistic accuracy with communicative fluency. Furthermore, the research explores recent innovations such as digital language learning platforms, gamification, and immersive cultural experiences that have transformed instructional practices. By integrating technology with traditional pedagogy, educators can create dynamic and learner-centered environments that promote both linguistic proficiency and cultural competence. The article concludes that effective Bahasa Indonesia instruction for non-native speakers requires a holistic approach that aligns curriculum design, teaching methods, and assessment practices with learner needs, while leveraging technological advancements and cultural immersion opportunities. This study provides valuable insights for language educators, curriculum developers, and policymakers, contributing to the advancement of Indonesian language education in both domestic and international contexts.